Beating a dead horse: investigating the continued use of ineffective assessment practices in modern education systems - Mohammad Awad AlAfnan; Siti Fatimah MohdZuki; Shefa Mohammad AlAfnan (International Journal of Evaluation and Research in Education (IJERE), 2026)
The study examines the persistence of outdated assessment practices in the education systems of Jordan, Malaysia, and Australia, utilizing the Dead Horse Theory as an interpretive lens. Despite ongoing educational reforms advocating for authentic, student-centered assessment models, traditional high-stakes and summative evaluations continue to dominate. The research adopts a qualitative multi-site case study approach, drawing data from semi-structured interviews, document analysis, and classroom observations. The 30 participants, including teachers, administrators, faculty, and policy analysts, were purposively selected across the three countries. Findings reveal three interconnected themes contributing to assessment stagnation: institutional inertia, cultural attachment to standardized metrics, and inadequate professional development. In Australia, systemic accountability pressures, such as National Assessment Program–Literacy and Numeracy (NAPLAN) and Australian Tertiary Admission Rank (ATAR) rankings, limit the innovation in assessment. In Jordan, the Jordanian High School General Examination (Tawjihi) exam significantly influences pedagogy and curriculum. In contrast, a dual reality prevails in Malaysia, with reform attempts often overshadowed by entrenched examination cultures. Teachers across all contexts expressed frustration with superficial policy changes and limited practical support, frequently engaging in performative compliance rather than genuine transformation. Applying the Dead Horse Theory highlights how education systems adopt symbolic or cosmetic reforms, ‘buying a stronger whip’ or ‘changing the rider’, instead of abandoning dysfunctional practices. The study concludes that meaningful reform requires structural and policy change, cultural shifts, and sustained teacher empowerment. The Dead Horse Theory thus serves as a powerful metaphor and diagnostic tool for identifying the illusion of progress and advocating for truly transformative educational assessment.